2021
DOI: 10.3390/ijms22010398
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Central Type-1 Cannabinoid Receptor Gene Regulation in Food Intake and Eating Behaviors

Abstract: Different neuromodulatory systems are involved in long-term energy balance and body weight and, among these, evidence shows that the endocannabinoid system, in particular the activation of type-1 cannabinoid receptor, plays a key role. We here review current literature focusing on the role of the gene encoding type-1 cannabinoid receptors in the CNS and on the modulation of its expression by food intake and specific eating behaviors. We point out the importance to further investigate how environmental cues mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 162 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…According to the behavioral data, the significant overexpression of the genes encoding PPARα and PPARγ was observed in the brain of adult fish treated with CAU, along with an upregulation of the genes Cnr1 and Cnr2 , encoding type 1 (CB1) and type 2 (CB2) cannabinoid receptors, respectively ( Figure 3 a). Cnr1 was especially upregulated, supporting its major role in regulating eating behavior and energy balance related to food availability [ 23 ]. The existence of a cross-talk between orexinergic (hypocretinergic) and endocannabinoid systems has been reported in the literature, with both systems having common physiological functions in the regulation of appetite and reward [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the behavioral data, the significant overexpression of the genes encoding PPARα and PPARγ was observed in the brain of adult fish treated with CAU, along with an upregulation of the genes Cnr1 and Cnr2 , encoding type 1 (CB1) and type 2 (CB2) cannabinoid receptors, respectively ( Figure 3 a). Cnr1 was especially upregulated, supporting its major role in regulating eating behavior and energy balance related to food availability [ 23 ]. The existence of a cross-talk between orexinergic (hypocretinergic) and endocannabinoid systems has been reported in the literature, with both systems having common physiological functions in the regulation of appetite and reward [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies demonstrated that both enhanced endocannabinoid tone and increased CB1 expression in the hypothalamus are transitory and characteristic only of the early phases of exposure to HFD [100]. In the same area, other studies displayed altered expression of CB2 [101], NAPE-PLD, and DAGLa [102]. Additionally, significant gender differences were found in these results [100,102], suggesting the existence of sex-specific variations.…”
Section: Endocannabinoid System Physiopathology In Obesity and Food Addictionmentioning
confidence: 94%
“…Unfortunately, except for SM-11 [182], no molecule so far has been tested in a model of food addiction, and there is a notable lack of information about the capability of these molecules to act on the reward system. However, the ECS has a well-recognized role in addictions [101], and targeting it could be beneficial towards efforts to re-establish reward alterations related to disrupted eating behavior [9], even though further studies would be required to assess the role of the cited molecules in reward system impairments.…”
Section: Compound7mentioning
confidence: 99%
“…The modulation of the HPG axis by environmental cues such as stressors or diet reveals the interplay between different neuronal networks and signaling pathways including the ECS [11]. Reproduction strongly depends on energy homeostasis, especially in females [137] and endocannabinoids are well-known regulators of food intake and gut-brain communications [11,[138][139][140]. The possible interplay between estrogen and cannabinoid signaling has been evaluated in ovariectomized female guinea pigs through the use of the CB1 receptor agonists WIN 55,212-2, EB, and the specific agonists of ERα, ERβ, mERs, and GPR30 (PPT, DPN, STX, and G-1 respectively).…”
Section: The Ecs-dependent Modulation Of Gnrh and The Interplay With Estrogensmentioning
confidence: 99%